PUMP AND DUMP CRIMINAL OVERVIEW ACCORDING TO CAPITAL MARKET LAW NO. 8 YEAR 1995 - Rinaldi Agusta Fahlevie; Erita Oktasari; Bernadete Nurmawati; Puguh Aji Hari Setiawan; Johand Aldo Dimalouw (Awang Long Law Review, 2022)
This study aims to look at the Juridical Review of the Pump and Dump crime in capital market transactions on the Indonesia Stock Exchange based on the Capital Market Law. The main problem that the author discusses and analyzes in this research is the form of the Pump and Dump crime in capital market transactions on the Indonesia Stock Exchange based on the Capital Market Law and the proof of the Pump & Dump crime in the capital market (Case Study of TAXI and LUCK Issuers). The research method is a normative legal research method with a law approach and a case approach. Based on the analysis and provisions of the Capital Market Law, the author concludes that the Pump and Dump crime in capital market transactions on the Indonesia Stock Exchange, can be seen in its form based on certain patterns and methods. The form of the pump and dump pattern and method is in accordance with the elements of market manipulation as stipulated in the provisions of Articles 90 to 93 of the Capital Market Law. To prove that a pump and dump crime has occurred, evidence can be used as regulated in the Criminal Procedure Code.